RETRACTED: Calcium versus oral contraceptive pills containing drospirenone for the treatment of mild to moderate premenstrual syndrome: A double blind randomized placebo controlled trial. (March 2016) - Shehata, Nesreen A.A.
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Editorial Board for the following reason: This single-author publication which reports the conducting of a large 3-arm randomised controlled trial, with no missing data from 210 recruited patients, has been questioned as implausible. The authors have been unable to provide supporting documents to provide an explanation.